Hop timing of split step and kinematics analysis of lower extremities in badminton start footwork - Hsueh, Y.-C.; Pan, K.-M.; Tsai, C.-L. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to compare the split timing, and lower extremity kinetics of badminton players during push-off steps in six directions. Eight collegiate elite male badminton players received the random shot from an opponent in one of six directions. Result: Hop timing was 0.014-0.037 sec after the opponent struck the shuttlecock. The leg that was opposite the movement direction showed significantly greater tower extremity horizontal push-off force than the other leg did. Conclusion: The hop timing of split step simultaneous with the opponent skiking the shufflecock. The leg opposite the movement direction was the main push leg. When lower extremities exhibit the correct pushing direction and reach the peak push off force within 0.3 sec after the opponent strikes the shuttlecock, players should have more effective return in badminton .